REKAYASA PERANGKAT LUNAK MOBILE LIBRARY DI PERPUSTAKAAN TRISAKTI SCHOOL OF MANAGEMENT - Yulianah Yulianah; Wisnu Ananta Kusuma; Sri Wahjuni (Perpustakaan Nasional RI, 2019)
Introduction. This study aims to develop prototype of mobile library application as recommendation model to be applied in college libraries to provide easiness and velocity of information access for users by smartphone. This study took case in Trisakti School of Management Library that uses SLiMS software as its library application.Data Collection Method. This research uses software engineering approach with protyping adopted from Laudon (2016), consist of indentify basic requirements, develop working prototype, use the prototype, revise and enchance the prototype.Analysis Data. Software engineering uses Android platform.Results and Discussions. The study results show that there are six main basic requirements of mobile library applications that can be implemented in TSM Library, including online catalog, library account, renew, borrow, reserve, and journal. By using prototype, users can perform 8 tasks, include login, view personal library account, renew, searching of books, borrow book, reserve book, cancel of reserve, and searching of journals. The final testing results show that all functions of prototype run well without error.Conclusions. This research has succeeded in developing prototype of mobile library application which can be used as a model that is suitable to be applied in college libraries, especially TSM Library.